The Effectiveness of The Implementation of Guarantee Foreignation in Default Cases of Debts and Receivables - Aisyah Pratiwi, Dinar; Risma Dewi Hermawan (Universitas Duta Bangsa Surakarta, 2022)
the implementation of the agreement often does not run smoothly as promised. While the agreement has been made by the parties on the legal basis of the agreed agreement, where there are rights and obligations of the parties. Article 1313 of the Civil Code states: â€œa covenant is an act by which one or more persons bind themselves to one or more other personsâ€. The occurrence of a promise injury or default results in the other party being harmed. Before the judge who examines and adjudicates the case and gives the verdict, the parties involved can apply for a security seizure (convesatoir beslaag) against an object/property that is the object of the case. The type of research conducted in this study is normative descriptive research. With the study of literature sourced legislation, books, journals, papers related to the title under study